(Hyper)tension release by N-terminal acetylation. Issue 8 (August 2015) - Aksnes, Henriette; Drazic, Adrian; Arnesen, Thomas
Abstract : A recent study links N-terminal acetylation and N-end rule degradation to blood pressure regulation. N-terminal mutants of Rgs2, a key G-protein regulator, are differentially processed by N-terminal acetyltransferases and the two branches of the N-end rule pathway. This leads to an imbalance in the signaling governing blood pressure.